Essential Role of the a3 Isoform of V-ATPase in Secretory Lysosome Trafficking via Rab7 Recruitment - Naomi Matsumoto (Nature Portfolio, 2018)
Abstract Secretory lysosomes are required for the specialised functions of various types of differentiated cells. In osteoclasts, the lysosomal proton pump V-ATPase (vacuolar-type ATPase) is targeted to the plasma membrane via secretory lysosomes and subsequently acidifies the extracellular compartment, providing optimal conditions for bone resorption. However, little is known about the mechanism underlying this trafficking of secretory lysosomes. Here, we demonstrate that the lysosome-specific a3 isoform of the V-ATPase a subunit plays an indispensable role in secretory lysosome trafficking, together with Rab7, a small GTPase involved in organelle trafficking. In osteoclasts lacking a3, lysosomes were not transported to the cell periphery, and Rab7 was not localised to lysosomes but diffused throughout the cytoplasm. Expression of dominant-negative (GDP-bound form) Rab7 inhibited lysosome trafficking in wild-type cells. Furthermore, a3 directly interacted with the GDP-bound forms of Rab7 and Rab27A. These findings reveal a novel role for the proton pump V-ATPase in secretory lysosome trafficking and an unexpected mechanistic link with Rab GTPases.